PENGARUH KESELAMATAN, KESEHATAN DAN KEDISIPLINAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN WORKSHOP PT. IRADAH DELAPAN - MUHAMMAD RAFSANJANI ROMADHON (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
Efforts to improve the quality of human resources, the main source of human companies need to be done well, directed, and planned, so that companies can compete fairly with other companies, given the future competition between companies will be more stringent. Human resources are able to compete with competitors or with business partners the only company that has the quality of human resources. The research objective was to determine the effect of work safety, health and work discipline on the performance of employees of PT. Eight Iradah Workshop Division. This study uses a survey method using primary data obtained from the questionnaire. The sample in this study was 57 PT. Eight Iradah Workshop Division. Samples taken using saturated sampling are sampling techniques based on the total population. Data were analyzed using multiple linear regression. The results showed that: (1) Work Safety had a significant positive effect on employee performance. (2) Health Work has no effect which has a significant positive effect on employee performance. (3) Discipline of significant positive effects on employee performance.